PENDIDIKAN EMOSIONAL ANAK DALAM KELUARGA - Bermi, Wibawati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2019)
The family is an important position among social institutions that have concern for children. The family must be able to prepare a good generation for the future, because the family is a small scope that can bring someone a good social life. Good social order is influenced by family conditions. Society is a collection of reflections from the lifestyle, world view, even the perspective of each individual in the family. The family plays a very important role in directing children to become a generation of good morality and benefit the community.